P06.05 IDO1-deleted CAR T cells show improved therapeutic efficacy in murine pancreatic cancer models. (1st October 2020) - Senz, AM; Metzger, P; Rubens, RK; Cadilha, B; Kirmaier, M; Lesch, S; Benmebarek, MR; Theurich, S; Murray, P; Endres, S; Kobold, S; König, LM; et al.
Abstract : Background: Indoleamine-2, 3-dioxygenase 1 (IDO1) is a cytosolic enzyme that catalyzes the rate limiting reaction in the kynurenine pathway. Dendritic cells, macrophages and several tumor entities have been described to express IDO1. In the tumor microenvironment IDO1 promotes tryptophan starvation and accumulation of kynurenines which result in T effector cell proliferation arrest and T regulatory cell induction. Additionally, IDO1 possesses two immunoreceptor tyrosine-based inhibitory motifs (ITIM) that upon phosphorylation can act as docking sites for the recruitment and activation of the tyrosine phosphatases SHP–1 and SHP–2 and ultimately to an activation of the non-canonical NF-ΚB pathway. Whether IDO1 is expressed in T cells and its potential function is unknown. Materials and Methods: Using IDO1-deleted splenocytes from CD4-Cre Ido1 fl/fl mice and WT controls, we evaluated the induction of IDO1 in T cells, as well as the effect of IDO1 in T cell proliferation, differentiation and metabolism. Additionally, we compared in vitro and in vivo the cytotoxic activity of anti-epithelial cell adhesion molecule (EpCAM) chimeric antigen receptor (CAR) T cells using pancreatic tumor cell lines. Results: IDO1 is inducible in primary mouse T cells upon T cell activation and type I and type II interferon signaling. Interestingly, the use of IDO1 knockout CAR T cells prolongs survival and improves tumor control compared to WT CAR T cell treatment in subcutaneous and orthotopic pancreatic cancer models. In vitro, T cell proliferation, differentiation and cytotoxic function is comparable in WT and IDO1-deleted T cells. RNA sequencing, metabolic and in vivo tracking studies are currently being performed to pin down IDO1-intrinsic effects on CAR T cells. Conclusions: IDO1 is expressed in T cells upon T cell receptor and IFN stimulation and appears to negatively affect tumor control mediated by CAR T cells. Specific IDO1 deletion may improve therapeutic efficacy of CAR T cells in solid tumors, such as pancreatic cancer. Disclosure Information: A.M. Senz: None. P. Metzger: None. R.K. Rubens: None. B. Cadilha: None. M. Kirmaier: None. S. Lesch: None. M.R. Benmebarek: None. S. Theurich: None. P. Murray: None. S. Endres: None. S. Kobold: None. L.M. König: None. P. Duewell: None. M. Schnurr: None.